Characterising the microbial profiles of various river sources and investigating the efficacy of UV radiation to reduce microbial loads for improved crop safety - Bursey, Caroline Rose (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScFoodSc)--Stellenbosch University, 2021.